2011
DOI: 10.1111/j.1600-048x.2011.05333.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration phenology and winter habitat quality are related to circulating androgen in a long-distance migratory bird

Abstract: In migratory birds, the timing of departure from wintering grounds is often dependant on the quality of habitat on an individual's territory and may influence individual fitness, resulting in an interaction of life history stages across large geographical distances. American redstart Setophaga ruticilla males who overwinter in high quality habitats arrive early to breed and subsequently produce more offspring than late arrivers. Since many migratory species overlap vernal migration with the physiological trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 64 publications
4
37
1
Order By: Relevance
“…Because testosterone stimulates territorial behavior, courtship and mating in male birds, increases in plasma T concentrations are an important indicator that males are preparing to breed (Wingfield et al 2001; Jodie et al 2007; Garamszegi et al 2008;McGlothlin and Ketterson 2008;Tonra et al 2011). Our results show that plasma T concentrations peaked earlier in the Asian Short-toed Lark than in the Eurasian Skylark in 2014, but at the same time in 2015.…”
Section: Changes Of Reproductive Hormonessupporting
confidence: 54%
“…Because testosterone stimulates territorial behavior, courtship and mating in male birds, increases in plasma T concentrations are an important indicator that males are preparing to breed (Wingfield et al 2001; Jodie et al 2007; Garamszegi et al 2008;McGlothlin and Ketterson 2008;Tonra et al 2011). Our results show that plasma T concentrations peaked earlier in the Asian Short-toed Lark than in the Eurasian Skylark in 2014, but at the same time in 2015.…”
Section: Changes Of Reproductive Hormonessupporting
confidence: 54%
“…Still, we are able to present patterns in the individual variation explained by conditional proxies and support for individual adjustments in timing of migration indicating individual strategies. Previous studies using stable-isotope analysis to investigate environmental conditions at the non-breeding grounds in relation to carry-over effects in the NearcticNeotropic system have shown that moist habitat conditions are generally associated with an early departure from the non-breeding grounds (Marra et al 1998;Studds and Marra 2005), improved body condition (Bearhop et al 2004;Marra et al 1998;Smith et al 2010), and an early arrival at the breeding site (Marra et al 1998;Norris et al 2004;Tonra et al 2011). However, a recent study suggests that this pattern may not hold for all species or even among individuals of the same species wintering in different regions (Gonzalez-Prieto and Hobson 2013).…”
Section: Timing Of Spring Migrationmentioning
confidence: 99%
“…In particular, winter habitat is known to influence spring migration timing and energetic condition (Bearhop et al 2004, Boone et al 2010, González-Prieto and Hobson 2013, Paxton and Moore 2015, Graham et al 2016. For example, American redstarts Setophaga ruticilla that over-winter in more xeric habitat depart later and in poorer condition for spring migration than those in more mesic habitat and this influences breeding arrival timing and condition (Marra et al 1998, Tonra et al 2011, McKellar et al 2013, Cooper et al 2015. For example, American redstarts Setophaga ruticilla that over-winter in more xeric habitat depart later and in poorer condition for spring migration than those in more mesic habitat and this influences breeding arrival timing and condition (Marra et al 1998, Tonra et al 2011, McKellar et al 2013, Cooper et al 2015.…”
Section: Introductionmentioning
confidence: 99%